Eksistensi Bendung Leko Pancing di Kabupaten Maros 1973-2016 - Nurhaidah Yusuf; Muh. Saleh Madjid; Jumadi Sahabuddin (Pendidikan Sejarah Fakultas Ilmu Sosial Fakultas Ilmu Sosial, 2017)
This Paper discusses Leko Pancing Dam in Maros district (1973-2016) which will be decomposed in several sub-material that is the background of the contruction of Leko Pancing Weir, the development of Leko Pancing Dam from the beginning of the development in 1973 until 2016 and the impact of the existence of Weir for the community. The Problem studied in this paper is Leko Pancing Dam located in Maros regency build in Maros District administration area but untilized as raw water source by PDAM Makassar thorough water treatment plant (IPA) Panaikang to fulfill the need of clean water of Makassar City community. The result of research shows that Leko Pancing Dam in Maros Regency development is in the background against the unavailability of surface water in Makassar city which can be used as a sourch of raw water that can be used as if the water source of PDAM Makassar in Panaikang Water Treatment Plant, and in Makassar only has one processing installation water is IPA I Ratulangi with a capacity of 50 liters/second that can not meet the need for clean water Makassar city community. Impact of existence of Leko Pancing Dam which reside in Maros Regency as raw water supply for three water Treatment Plant that is water treatment plant (IPA) II Panaikang, water treatment plant (IPA) III Antang, water treatment plant (IPA) II Pattontongan has benefits so that the need for clean water can be available although it can not be available althoughout the year because during the dry season the water supply from the lute of fishing lute is reducer and other problems such as public complaint that feel the water is less clean and sometimes smelly. Another impact is because water from the weir to the installation uses an open channel then the community uses its water to meet daily needs. This research is descriptive analysis using historis method. Through the stages of heuristics by finding sources related to researce either in the form books, brochures, or visiting the location of research and conduct interviews that have to do with research, the next stage of criticism both in the form of internal criticism and external critism to get historical facts about Leko Pancing weir in Maros district, from these facts which are further interpreted chronologically then presented in a historical writing.